Citizens' Position in Service Quality Perception. An Approach Analysis in the Case of Spanish Local Administrations - José L. VÁZQUEZ; Pablo GUTIÉRREZ; María P. GARCÍA (Transylvanian Review of Administrative Sciences, 2005)
Public sector organizations are not immune to pressure in order to improve their services to citizens. At this point, a major problem is that of “citizen-customer” satisfaction surveys being prone to focus on individuals’ perceptions on service delivery: what the individual think about the quality of delivered service. Authors have usually considered tools like the SERVQUAL scale (useful at measuring service quality in a diverse number of organizations and situations, both in private and public sector spheres) as a prior reference when researching in the quality field, but as being the “source”, then changed (modified) into a more or less “new” proposal. Following this research guideline, in this paper a new model for measuring perceived quality level in local government activities is presented. Three dimensions are suggested for citizens to valuate service quality: technical, functional and overall features.